Influence of medroxyprogesterone acetate on breast milk fat, calcium and crematocrit - Collantes Cubas, Jorge Arturo (2014)
Objectives: To determine whether postpartum medroxyprogesterone acetate produces variation in levels of total fat, calcium and crematocrit of transitional and mature milk. Design: Transversal and comparative study. Setting: Hospital Regional de Cajamarca, Peru and Hospital Nacional Cayetano Heredia, Lima, Peru. Participants: Lactating mothers. Interventions: In 1998 79 samples of maternal milk of mothers three months post partum were analyzed al Hospital Nacional Cayetano Heredia. These women either received medroxyprogesterone acetate (24) or not (55 controls). Total fat , calcium and crematocrit were determined. Main outcome measures: Total fat, calcium and crematocrit values. Results: In women receiving medroxyprogesterone acetate total fat levels were 4.8 +- 2.3 g/dL, and in controls, 4.6 +- 2.9 g/dL; calcium levels were respectively 55.6 +- 23.9 mg/ dL in cases and 55.5 mg/dL in controls; and crematocrit, 10.6 +- 3.8 in cases and 11.7 +- 4.4% in controls. There were no significant differences. Conclusions: Medroxyprogesterone acetate did not alter breast milk fat, calcium and crematocrit levels in the first three months postpartum.Keywords: Medroxyprogesterone, postpartum, breast milk, crematocrit, calcium, fats.